Subject-based feature extraction by using fisher WPD-CSP in brain–computer interfaces. Issue 129 (June 2016) - Yang, Banghua; Li, Huarong; Wang, Qian; Zhang, Yunyuan
Highlights: A subject-based feature extraction method is discussed. The feature extraction method combines wavelet packet decomposition, common spatial patterns and fisher distance. The selection of sub-bands based on fisher distance tells apart those useless sub-bands and remain best sub-bands for each subject. The proposed method can extract suitable features for specific subject and achieve a higher classification accuracy than non-subject-based method. Abstract: Background and objective: Feature extraction of electroencephalogram (EEG) plays a vital role in brain–computer interfaces (BCIs). In recent years, common spatial pattern (CSP) has been proven to be an effective feature extraction method. However, the traditional CSP has disadvantages of requiring a lot of input channels and the lack of frequency information. In order to remedy the defects of CSP, wavelet packet decomposition (WPD) and CSP are combined to extract effective features. But WPD-CSP method considers less about extracting specific features that are fitted for the specific subject. So a subject-based feature extraction method using fisher WPD-CSP is proposed in this paper. Methods: The idea of proposed method is to adapt fisher WPD-CSP to each subject separately. It mainly includes the following six steps: (1) original EEG signals from all channels are decomposed into a series of sub-bands using WPD; (2) average power values of obtained sub-bands are computed; (3) the specified sub-bands with larger values of fisher distance according to average power are selected for that particular subject; (4) each selected sub-band is reconstructed to be regarded as a new EEG channel; (5) all new EEG channels are used as input of the CSP and a six-dimensional feature vector is obtained by the CSP. The subject-based feature extraction model is so formed; (6) the probabilistic neural network (PNN) is used as the classifier and the classification accuracy is obtained. Results: Data from six subjects are processed by the subject-based fisher WPD-CSP, the non-subject-based fisher WPD-CSP and WPD-CSP, respectively. Compared with non-subject-based fisher WPD-CSP and WPD-CSP, the results show that the proposed method yields better performance (sensitivity: 88.7 ± 0.9%, and specificity: 91 ± 1%) and the classification accuracy from subject-based fisher WPD-CSP is increased by 6–12% and 14%, respectively. Conclusions: The proposed subject-based fisher WPD-CSP method can not only remedy disadvantages of CSP by WPD but also discriminate helpless sub-bands for each subject and make remaining fewer sub-bands keep better separability by fisher distance, which leads to a higher classification accuracy than WPD-CSP method.